2011
DOI: 10.1016/j.bone.2011.03.765
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of low bone mass in young patients with thalassemia by DXA, pQCT and markers of bone turnover

Abstract: Previous reports using dual x-ray absorptiometry (DXA) suggest that up to 70% of adults with thalassemia major (Thal) have low bone mass. However, few studies have controlled for body size and pubertal delay, variables known to affect bone mass in this population. In this study, bone mineral content and areal density (BMC, aBMD) of the spine and whole body were assessed by DXA, and volumetric BMD and cortical geometries of the distal tibia by peripheral quantitative computed tomography (pQCT) in subjects with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The classification of patients into normal, osteopenia and osteoporotic categories, using QCT Z scores, was in better agreement with the assignment based on trabecular number (k ϭ 0.209, P ϭ .053) than the classification using DXA Z scores (k ϭ 0.145, P ϭ .12) (186). Another study employing peripheral QCT showed lower tibial trabecular volumetric BMD, cortical area, cortical bone mineral content, cortical thickness, periosteal circumference and section modulus Z-scores in thalassemic patients compared to controls (52).…”
Section: Peripheral Quantitative Computer Tomographymentioning
confidence: 89%
See 1 more Smart Citation
“…The classification of patients into normal, osteopenia and osteoporotic categories, using QCT Z scores, was in better agreement with the assignment based on trabecular number (k ϭ 0.209, P ϭ .053) than the classification using DXA Z scores (k ϭ 0.145, P ϭ .12) (186). Another study employing peripheral QCT showed lower tibial trabecular volumetric BMD, cortical area, cortical bone mineral content, cortical thickness, periosteal circumference and section modulus Z-scores in thalassemic patients compared to controls (52).…”
Section: Peripheral Quantitative Computer Tomographymentioning
confidence: 89%
“…Multiple risk factors are implicated in bone loss and have been previously described (49,50). There have been many studies describing the prevalence of reduced bone mass in thalassemia but direct comparison of individual studies is difficult (49,(51)(52)(53). The problem lies in the inconsistent use of DXA Z score, T score and areal BMD to describe patient cohorts.…”
Section: A Low Bone Mass and Strengthmentioning
confidence: 97%
“…Our data also confirmed that the total BMD of patients is lower compared to controls. There are published data in the literature which prove that osteoporosis is a well-recognized side effect in thalassemic patients and explain the molecular paths that are implicated in this procedure [8, 11, 16, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…All patients should have a bone density assessment by dual energy x-ray absorptiometry (DXA) performed annually beginning at age 10 years to evaluate for low bone mass. Treatment options for low bone density include optimization of vitamin D and zinc levels, encouragement of weight bearing activity, and possibly a trial of bisphosphonates [34, 38, 39]. …”
Section: Guidelines and Discussionmentioning
confidence: 99%